The determinants of savings rates in OECD countries: The role of private pensions - Pınar Fulya Gebeşoğlu; Hasan Murat Ertuğrul; Ümit Bulut (Central Bank Review (CBR), 2023)
The design of pension schemes is crucial in determining savings behavior. The impact of pension schemes on saving rates across countries remains to be an intriguing empirical question considering the complicated nature of the relationship between saving patterns and pension wealth. This paper investigates the effect of the private pension contributions on savings rates in 25 selected OECD countries between the period 2001-2019 by employing quantile regression analysis which takes the heterogeneity of the data into account and provides information about not only the midpoint but also the extreme points of the distribution. According to the results, the savings rate is negatively associated with private pensions at all quantile levels. The empirical findings indicate that pension contributions tend to be strong substitutes for voluntary savings in countries with low tendencies to save. This result is especially important for its policy design implications as the policy makers tend to provide incentives either in the form of tax reliefs or direct substitutions for private pension contributions with the motivation to raise domestic savings.
Keywords: E21; H55; I38; D31; D91; 330; Panel quantile regression analysis; Private pensions; Savings